The Plan of Union in New York - Nichols, Robert Hastings (Church history, 1936)
The history of the Plan of Union has been written largely under the influence of denominational zeal, jealousy, and antipathy. Underlying much of the writing have been the assumptions that a main object of religious endeavor is to build up denominational organizations and enlarge the statistics, that denominations ought to be kept “pure,” that movements of individuals or churches from one to another are not altogether creditable and justify suspicion of inferior motives on the part of somebody. For example, the Rev. James H. Dill, in an article on “Congregationalism in Western New York” in the Congregational Quarterly in 1859, which has recently been cited as an authority, refers to churches “which have been spirited away from Congregationalism”; and Dr. Joseph P. Thompson, in an article on “Congregationalism in Eastern New York” in the same periodical in 1860, says “The Black River Association … had increased to seventeen churches when in 1817, it was induced to unite with the Watertown Presbytery. … After some years, some of the Congregational churches withdrew from this entanglement, and re-organized in an Association.” On the other side, Dr. Samuel J. Baird in 1868 said in A History of the New School, “The multiplication of Congregational ministers, in the Presbyterian Church, was no increase of strength; but the introduction of an element of weakness, division and heresy.”